Redistribution over the lifetime in the Irish tax-benefit system: an application of a prototype dynamic microsimulation model for Ireland - O'Donoghue, Cathal (Economic & Social Studies, 2001)
This paper examines the distribution of lifetime income in Ireland. To do this a new prototype dynamic microsimulation model for Ireland is used to generate lifetime income streams. Aggregating over the lifetime we can assess the distribution of lifetime income and the degree of redistribution in the tax-benefit system. In addition to the effect of taxes and benefits, we decompose lifetime income into its components and examine the impact of different life-cycle patterns.
Keywords: Lifetime income; Redistribution; Tax-benefit system; Ireland; Income distribution